Spectrophotometric analysis of two eye preparations, vial and drops, containing ketorolac tromethamine and phenylephrine hydrochloride binary mixture and their ternary mixture with chlorphenirmaine maleate - Marwa A.A. Ragab; Fawzy A. El Yazbi; Ekram M. Hassan; Essam F. Khamis; Mohamed M.A. Hamdy (Bulletin of Faculty of Pharmacy Cairo University, 2018)
Ketorolac tromethamine, KTC and phenylephrine hydrochloride, PHE binary mixture is co-formulated as eye vial, while their ternary mixture with chlorpheniramine maleate is co-formulated as eye drops. The existing work utilizes different spectrophotometric methods which are considered to be simple and rapid for the determination of both mixtures. These methods include: zero-order (D0), first derivative (D1), derivative (DR) or difference ratio (R.D), delta absorbance (ΔA) and finally convolution of derivative data using discrete Fourier functions (FFD). In the binary mixture, KTC is assayed using D0, D1 and ΔA methods with no interference from PHE, while PHE needed some spectroscopic treatments for its analysis due to the spectral overlap of KTC with its maximum wavelength (λmax) at 273 nm. Such treatments involve D1 R.D, D2R, FFD2 and ΔA methods. In the ternary mixture, KTC is assayed using D0 and D1 with no interference from both PHE and CPM, while R.D, D1R and FFD2 are used to assay both PHE and CPM to resolve the overlap in their spectra. Linear regression lines were obtained over the concentration ranges 1–18 and 6–48 μg.mL−1 for KTC and PHE (binary mixture), respectively and 2–9, 1–18 and 2–9 μg.mL−1 for CPM, KTC and PHE (ternary mixture), respectively yielding high correlation coefficients values (higher than 0.999). The lowest LOQ value for KTC (0.46 μg.mL−1) was obtained upon using the D1 method in the binary mixture while the R.D method yielded the lowest LOQ values for both PHE (0.34 μg.mL−1) and CPM (0.97 μg.mL−1) in the ternary mixture.